THE EFFECTIVENESS OF SOROGAN AND BANDONGAN LEARNING METHODS IN IMPROVING THE ACHIEVEMENT OF STUDENT LEARNING OUTCOMES IN BMK SUBJECTS (GUIDANCE FOR READING BOOKS) - Nasta’in, Muhammad; Mu’id, Abdul (Al-Mubin, 2025)
This The teaching of classical Islamic texts (kitab kuning) in Islamic educational institutions has long relied on two traditional methods: bandongan (lecture-based group learning) and sorogan (individualized tutorial learning). Both approaches play a crucial role in enhancing students comprehension of the texts. This study aims to analyze the effectiveness of these methods in the learning process of the Guided Book Reading (GBR) subject, particularly among students of the Sifir Robi’ A class at the Islamic Elementary School for Classical Text Studies (Madrasah Diniyah) of the Qomaruddin Islamic Boarding School (Pondok Pesantren Qomaruddin), located in Sampurnan, Bungah, Gresik, Indonesia. The research focuses on the implementation of the bandongan and sorogan methods, their influence on learning outcomes, and the academic achievement of the students. This study employed a Classroom Action Research (CAR) approach, carried out in three stages. The preliminary stage (pre-cycle) utilized the bandongan method, while the sorogan method was applied during Cycle I and Cycle II. Each stage followed four procedures: planning, action implementation, observation, and reflection. The findings revealed that the average student score using the bandongan method was 67.17, with a learning mastery rate of 25%. After the application of the sorogan method in Cycle I, the average score rose to 68.75, and the mastery rate increased to 66.67%. Further improvement occurred in Cycle II, with a significant increase in the average score and a mastery rate reaching 70%. These results indicate that the sorogan method is more effective in enhancing students academic performance compared to the bandongan method. Therefore, the sorogan approach is considered a more effective strategy for the teaching of Guided Book Reading (GBR) within the context of Islamic boarding school education